Mechanismy působení nízkomolekulárních a vysokomolekulárních cyto-protektivních látek při vystavení hmyzího organismu nízkým teplotám. - Hůla, Petr (Jihočeská univerzita, 2023)
Low temperatures limit the viability of cells, tissues and whole organisms. Temperate and polar insects overwinter with body temperatures below 0°C, sometimes with ice crystals in their hemolymph. Extracelular freezing is linked with cell osmotic dehydration. Thus, the freeze-tolerant insects had to evolve complex adaptation, including seasonal accumulation of low- and high-molecular substances, to protect their tissues against deleterious effects of cell freeze-dehydration. The mechanisms by which different substances exert their cryoprotective roles are theoretically diverse but practically poorly studied. In this thesis, I present results of metabolomic and transcriptomic analyses of putative cryoprotectants in the freeze-tolerant larvae of drosophilid fly, Chymomyza costata that accumulate in their hemolymph and tissues in response to cooling and drying. The functional aspects of low- (mainly proline and trehalose) and high- molecular substances (mainly LEA-like proteins) are considered.
The mechanisms of low and high molecular weight cyto-protective compounds during exposure of insects to low temperatures.